2013
DOI: 10.1155/2013/152656
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcome of Japanese Encephalitis in Children Admitted with Acute Encephalitis Syndrome

Abstract: Japanese encephalitis (JE) is an arthropod borne viral disease. Children are most commonly affected in Southeast Asian region showing symptoms of central nervous system with several complications and death. The clinical characteristics and outcomes in pediatric JE patients hospitalized with acute encephalitis syndrome (AES) are still poorly understood. A prospective study was conducted in pediatric ward of Assam Medical College Hospital to evaluate the clinical profile and outcome of JE in children. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
36
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 20 publications
11
36
3
3
Order By: Relevance
“…It could be explained by younger patients were more affected probably because of lack of cumulative immunity due to natural infection. A male preponderance was seen in our study which was similar with various earlier studies (8,9,10,15). It could be explained probably due to males are exposed more in outdoor activities in regards to females who mostly stay indoors.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It could be explained by younger patients were more affected probably because of lack of cumulative immunity due to natural infection. A male preponderance was seen in our study which was similar with various earlier studies (8,9,10,15). It could be explained probably due to males are exposed more in outdoor activities in regards to females who mostly stay indoors.…”
Section: Discussionsupporting
confidence: 93%
“…Seizure was seen in (43.3%) cases. Similar observations were made by different researchers in earlier studies (8,9,10,12). In our study, after detailed evaluation of all laboratory investigation reports , it was found that the most common cause of AES was acute ( Non JE) encephalitis (78.3%) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations